Autism and developmental disability caused by KCNQ3 gain‐of‐function variants. Issue 2 (26th June 2019) - Sands, Tristan T.; Miceli, Francesco; Lesca, Gaetan; Beck, Anita E.; Sadleir, Lynette G.; Arrington, Daniel K.; Schönewolf‐Greulich, Bitten; Moutton, Sébastien; Lauritano, Anna; Nappi, Piera; Soldovieri, Maria Virginia; Scheffer, Ingrid E.; et al.
Abstract : Objective: Recent reports have described single individuals with neurodevelopmental disability (NDD) harboring heterozygous KCNQ3 de novo variants (DNVs). We sought to assess whether pathogenic variants in KCNQ3 cause NDD and to elucidate the associated phenotype and molecular mechanisms. Methods: Patients with NDD and KCNQ3 DNVs were identified through an international collaboration. Phenotypes were characterized by clinical assessment, review of charts, electroencephalographic (EEG) recordings, and parental interview. Functional consequences of variants were analyzed in vitro by patch‐clamp recording. Results: Eleven patients were assessed. They had recurrent heterozygous DNVs in KCNQ3 affecting residues R230 (R230C, R230H, R230S) and R227 (R227Q). All patients exhibited global developmental delay within the first 2 years of life. Most (8/11, 73%) were nonverbal or had a few words only. All patients had autistic features, and autism spectrum disorder (ASD) was diagnosed in 5 of 11 (45%). EEGs performed before 10 years of age revealed frequent sleep‐activated multifocal epileptiform discharges in 8 of 11 (73%). For 6 of 9 (67%) recorded between 1.5 and 6 years of age, spikes became near‐continuous during sleep. Interestingly, most patients (9/11, 82%) did not have seizures, and no patient had seizures in the neonatal period. Voltage‐clamp recordings of the mutant KCNQ3 channels revealed gain‐of‐function (GoF) effects. Interpretation: Specific GoF variants in KCNQ3 cause NDD, ASD, and abundant sleep‐activated spikes. This new phenotype contrasts both with self‐limited neonatal epilepsy due to KCNQ3 partial loss of function, and with the neonatal or infantile onset epileptic encephalopathies due to KCNQ2 GoF. ANN NEUROL 2019;86:181–192